Influence of Injection Pressure on the Thermohydrodynamic Behavior of Tilting Pad Journal Bearings—Model and Experiment. Issue 3 (4th May 2021) - Bizarre, L.; Daniel, G. B.; Santos, I. F.; Cavalca, K. L.
Abstract: In rotating machines, tilting pad journal bearings (TPJBs) are widely used because of their enhanced design stability in comparison with alternative bearing configurations. In the present research, a thermohydrodynamic (THD) lubrication model for a tilting pad bearing with injection is developed. Within the THD lubrication model, the lubricant is also fed into each pad through a central injection orifice. The effects on the lubricant oil film pressures and temperatures and subsequent influences on the system dynamic behavior were investigated. Another important factor considered within the THD model is associated with the flexibility of the pivot of each pad and its impact on the behavior of the bearing when subjected to direct lubricant injection. The numerical model results are compared with the measurements of the rotor equilibrium position within the bearing and the pad temperatures obtained from the test rig designed specifically for the TPJB geometry with and without central pad injection. Pad temperatures are measured before the injection orifice position and after it. Agreement between experimental and model-predicted results provides confidence in the model's ability to evaluate the dynamic behavior of the bearing and its effect on the complete system through the stiffness and damping coefficients.